2018
DOI: 10.1002/adma.201800191
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Ammonia Synthesis via Nitrogen Reduction Reaction on a MoS2 Catalyst: Theoretical and Experimental Studies

Abstract: The discovery of stable and noble-metal-free catalysts toward efficient electrochemical reduction of nitrogen (N ) to ammonia (NH ) is highly desired and significantly critical for the earth nitrogen cycle. Here, based on the theoretical predictions, MoS is first utilized to catalyze the N reduction reaction (NRR) under room temperature and atmospheric pressure. Electrochemical tests reveal that such catalyst achieves a high Faradaic efficiency (1.17%) and NH yield (8.08 × 10 mol s cm ) at -0.5 V versus revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
527
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 760 publications
(572 citation statements)
references
References 47 publications
17
527
0
1
Order By: Relevance
“…MoS 2 , one of the layered sulfide materials with low‐cost and nontoxicity, also used as electrocatalysts for NRR . A study has demonstrated that a MoS 2 NS array is also active for NRR, but it suffers from relatively low electrical conductivity with an FE of 1.17% . However, Li et al demonstrated that greatly boosted electrocatalytic N 2 reduction to NH 3 by using MoS 2 NSs‐rGO hybrid under ambient conditions.…”
Section: Electrochemical N2 Reductionmentioning
confidence: 99%
“…MoS 2 , one of the layered sulfide materials with low‐cost and nontoxicity, also used as electrocatalysts for NRR . A study has demonstrated that a MoS 2 NS array is also active for NRR, but it suffers from relatively low electrical conductivity with an FE of 1.17% . However, Li et al demonstrated that greatly boosted electrocatalytic N 2 reduction to NH 3 by using MoS 2 NSs‐rGO hybrid under ambient conditions.…”
Section: Electrochemical N2 Reductionmentioning
confidence: 99%
“…From the thermodynamics point of view, *NNH is usually deemed as a key intermediate during the NRR process. A number of simulation studies on NRR catalysts including NiO have substantiated that the first proton‐coupled electron transfer to generate *NNH (*N 2 →*NNH) is the potential determining step (PDS) of the overall NRR. Thus, an effective NRR catalyst should facilitate *NNH formation/stabilization.…”
Section: Figurementioning
confidence: 99%
“…[58,59] The calibration curve for NH 3 assay was presented in Figure S6 in the Supporting Information. The NRR electrocatalytic activities of Ti 3 C 2 T x on the CP (Ti 3 C 2 T x -CP) were also studied for comparison.…”
mentioning
confidence: 99%